2022
DOI: 10.3390/insects13111008
|View full text |Cite
|
Sign up to set email alerts
|

Using MaxEnt to Predict the Potential Distribution of the Little Fire Ant (Wasmannia auropunctata) in China

Abstract: Invasive ants are some of the most destructive species in ecosystems and can have serious ecological and socioeconomic impacts. The little fire ant, Wasmannia auropunctata, is native to Central and South America and was listed as one of the 100 most threatening major invasive organisms in the world by the International Union for Conservation of Nature (IUCN). The presence of W. auropunctata was first reported on the Chinese mainland in January 2022, but its distribution in China is still unclear. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
(42 reference statements)
0
22
0
Order By: Relevance
“…majale , the most important were Bio17 and Bio2. The response curve between bioclimatic variables and the probability of a species’ presence reflects the relationship [ 48 ]. As shown in Figure S2 , with the temperature and precipitation change, the probability of the occurrence of a species was constantly changing, and the relatively suitable environmental conditions also corresponded to the potential distribution in China.…”
Section: Resultsmentioning
confidence: 99%
“…majale , the most important were Bio17 and Bio2. The response curve between bioclimatic variables and the probability of a species’ presence reflects the relationship [ 48 ]. As shown in Figure S2 , with the temperature and precipitation change, the probability of the occurrence of a species was constantly changing, and the relatively suitable environmental conditions also corresponded to the potential distribution in China.…”
Section: Resultsmentioning
confidence: 99%
“…If the correlation was | r | ≥ 0.8 between two environmental variables (Fig. S2), the environmental variable with the lowest contribution rate was removed 25,26,37 . Ultimately, eight qualified environmental variables were selected for modeling (Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…19,21,22 To reduce overfitting caused by species distribution clustering, the buffer analysis tool in ArcGIS 10.8.1 was used to select species distribution points. Since the spatial resolution of the environmental variables used in the study was 2.5 arc-min (5 km), [23][24][25] the linear unit in the buffer was set to 2.5 km. Spatial refinement of the species distribution points was achieved by randomly retaining one distribution point within the overlapping buffer zone.…”
Section: Species Distribution Datamentioning
confidence: 99%
“…In January 2022, W. auropunctata was first discovered to have invaded Chinese mainland (Chen et al, 2022). Maxent niche modeling showed that most of the area south of the Yangtze River is potentially favorable for W. auropunctata, and temperature is the main factor affecting its distribution (Mao et al, 2022). Therefore, this species has the potential to impact biodiversity, especially that of ant communities, in southern China.…”
Section: Introductionmentioning
confidence: 99%